Effect of Neem Leaves (Azadirachta indica) as a Growth Promoter in Broiler Chickens - Sutradhar, Suman Kumar; Chatterjee, Jayanta Kumar; Chakrabortty, Partha Sarathi (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted from 1st February to 14th March, 2022 (42 days) at the Model Dairy & Poultry Farm, Institute of Agriculture (PSB), Visva-Bharati University, Sriniketan, Birbhum, (731236) West Bengal, India, to evaluate the effect of neem leaves powder supplementation on growth performance, feed consumption (FC), feed conversion ratio (FCR), and carcass quality traits of broiler chickens. The inclusion of 1% dry neem leaves powder in the diet was assessed for its pharmacologically active ingredients bioavailability. The results indicated that 1% dietary inclusion led to significantly better body weight, body weight gain, and feed conversion ratio at the 6th week of age compared to other treatment groups. The body weights at the 6th week were 1916±62.02, 2024±51.08, 2010±15.36, and 1893.4±27.95 g for T1 (control), T2 (1%), T3 (2%), and T4 (3%) respectively, showing significant differences (p<0.01) among treatments. The body weight gain values were 377.56±4.61, 394.28±5.16, 386.2±5.49, and 356.48±6.28 g for T1, T2, T3, and T4 respectively, with significant differences (p<0.01). The feed conversion ratio values were 1.85±0.05, 1.78±0.03, 1.82±0.03, and 1.98±0.04 in T1, T2, T3, and T4 respectively, also showing significant differences (p<0.01). However, no significant differences were observed in other parameters. The findings suggest that 1% neem leaves powder supplementation enhances growth performance and feed utilization in broiler chickens, making it a beneficial dietary addition compared to other inclusion levels.